Feasibility and Potential Benefits of a Web-Based Intervention Delivered Acutely After Mild Traumatic Brain Injury in Adolescents: A Pilot Study. Issue 6 (November 2016) - Kurowski, Brad G.; Wade, Shari L.; Dexheimer, Judith W.; Dyas, Jenna; Zhang, Nanhua; Babcock, Lynn
Abstract : Background: There is a paucity of evidence-based interventions for mild traumatic brain injury (mTBI). Objective: To evaluate the feasibility and potential benefits of an interactive, Web-based intervention for mTBI. Setting: Emergency department and outpatient settings. Participants: Of the 21 adolescents aged 11 to 18 years with mTBI recruited from November 2013 to June 2014 within 96 hours of injury, 13 completed the program. Design: Prospective, open pilot. Intervention: The Web-based Self-Management Activity-restriction and Relaxation Training (SMART) program incorporates anticipatory guidance and psychoeducation, self-management and pacing of cognitive and physical activities, and cognitive-behavioral principles for early management of mTBI in adolescents. Main Measures: Primary: Daily Post-Concussion Symptom Scale (PCSS). Secondary: Daily self-reported ratings of activities and satisfaction survey. Results: Average time from injury to baseline testing was 14.0 (standard deviation = 16.7) hours. Baseline PCSS was 23.6 (range: 0-46), and daily activity was 1.8 (range: 0-5.75) hours. Repeated-measures, generalized linear mixed-effects model analysis demonstrated a significant decrease of PCSS at a rate of 2.0 points per day that stabilized after about 2 weeks. Daily activities, screen time, and physical activity increased by 0.06 (standard error [SE] = 0.04, P = .09), 0.04 (SE = 0.02, P = .15), and 0.03 (SE = 0.02, P = .05) hours per day, respectively, over the 4-week follow-up. Satisfaction was rated highly by parents and youth. Conclusions: Self-Management Activity-restriction and Relaxation Training is feasible and reported to be helpful and enjoyable by participants. Future research will need to determine the comparative benefits of SMART and ideal target population.